2002
DOI: 10.1046/j.1472-765x.2002.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial status and rumen enzyme profile of crossbred calves fed on different microbial feed additives

Abstract: Aims: To test various microbial cultures as cattle feed additives. Methods and Results: Four groups of newly born crossbred calves (average body weight 23·5 kg) were reared on green berseem and calf starter which was devoid of cereal grains. Milk was fed up to 8 weeks of age, starting with one tenths and gradually reducing to one twentieths of the body weight. One hundred millilitres of microbial feed additive or 100 g fermented feed was fed to the animals of group 2 (curd containing lactic acid bacteria at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(83 citation statements)
references
References 19 publications
3
78
0
2
Order By: Relevance
“…On the other hand, the efficacy of probiotics depends on the adaptation of microbial species to the environmental conditions and their ability to survive and compete with pathogens in the gastrointestinal tract, and is closely related with the dose and microbial composition of the probiotic source. Different results from the studies using commercial or natural probiotic supplements with different doses of lactic acid bacteria and yeast have so far been obtained (Cruywagen et al, 1996;Agarwal et al, 2002;Ayışığı et al, 2005;Timmerman et al, 2005). The doses of kefir (1.2x10 9 cfu/kg LW) and the commercial probiotic source (2.15x10 5 cfu/kg LW) supplemented to kids in the present study were similar to the doses used in other studies reported in the literature.…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, the efficacy of probiotics depends on the adaptation of microbial species to the environmental conditions and their ability to survive and compete with pathogens in the gastrointestinal tract, and is closely related with the dose and microbial composition of the probiotic source. Different results from the studies using commercial or natural probiotic supplements with different doses of lactic acid bacteria and yeast have so far been obtained (Cruywagen et al, 1996;Agarwal et al, 2002;Ayışığı et al, 2005;Timmerman et al, 2005). The doses of kefir (1.2x10 9 cfu/kg LW) and the commercial probiotic source (2.15x10 5 cfu/kg LW) supplemented to kids in the present study were similar to the doses used in other studies reported in the literature.…”
Section: Discussionsupporting
confidence: 73%
“…Carboxymethylcellulase (CMCase) and xylanase activities were estimated as described earlier [14][15][16]. The reaction mixture used for the estimation of these enzymes contained: 1.0 mL phosphate buffer (pH 6.8, 0.1 M), 0.5 mL substrate (1% carboxymethylcellulose and 0.25% xylan from oat spelt) and 0.5 mL enzyme; incubated at 39 °C for 1 h for CMCase and 30 min for xylanase.…”
Section: Estimation Of Enzymesmentioning
confidence: 99%
“…There is a lot of variation in the performance of same animal fed on different species of probiotic, or even the same species but different strain of probiotic. Agarwal et al (2002) reported that NCDC-49 has proved to be the best in enhancing the performance of calves. However, few reports using limited strains are available on the performance of goats and there is a scope of further research using more specialised new strains.…”
Section: Introductionmentioning
confidence: 99%